A Study on Effectiveness of Leadership in a Public Sector Organization - Hema Lakshmi, H.; Sivasankar, P. R. (Prabandhan: Indian Journal of Management, 2013)
As the global economy gathers pace, more public sector organizations are realizing that their main assets are their people and that remaining or becoming competitive depends increasingly on the development of a highly skilled workforce. This requires trained and committed leaders but they, in turn, need the leadership of highly effective managers and the support of other senior and middle level leaders and managers. No single leadership is effective in all situations. Many different theories of leadership have been developed through years of research with groups and organizations. It explains that the style a leader chooses depends mostly upon the group’s level of readiness. That is, how willing and able the members are to take responsibility as a group. The present research article aims at analyzing the effectiveness of leadership in the public sector. The period of the study was from 2010-2011. The effectiveness of leadership in a public sector insurance giant was analyzed by working out the weighted mean and factor analysis.